“Hablemos del VIH/SIDA en la UEB” - Llivi Ruilova, Danny Vicente (2023)
The WORLD HIV/AIDS DAY DAY was held with enthusiasm, called “Let's talk about HIV/AIDS at the UEB”, an event organized by the Nursing program of the Faculty of Health and Human Sciences; with the assistance of Mgtr. Silvana López Paredes, Dean; Mgtr. María Olalla, head of Nursing; Dr. Santiago Pacheco, teacher; and medical staff of the Alfredo Noboa Montenegro Hospital.